Treatment of veterinary insecticide residues using biomixtures: performance, degradation kinetics, and ecotoxicological assessment - R. C. Pessagno; N. Olié; V. A. Silvani; R. P. Colombo; G. Svartz; A. Iriel (International Journal of Environmental Science and Technology, 2026)

Conversion of municipal biowaste into value-added products toward a circular bioeconomy: bridging the gap between laboratory-scale and full-scale implementation - José Manuel Alejandro Cerdán; Tatiana Kimura Kodama; G. H. D. Oliveira; Lucas Tadeu Fuess; Júlia Fonseca Colombo Andrade; Aldo Roberto Ometto (Clean Technologies and Environmental Policy, 2026)
Scaling-up municipal biowaste conversion technologies to industrial levels is essential for advancing clean and sustainable technologies and addressing significant technical, economic, and environmental challenges associated with urban organic waste management. Studies that explore technological gaps across the upstream, midstream, and downstream processing stages of biorefineries are critical for transforming biowaste into value-added products. This study aims to fill these gaps through a systematic literature review following the PRISMA guidelines and utilizing the Technology Readiness Level (TRL), which enabled the selection of 88 cases subsequently analyzed using descriptive and content analysis. The main findings show that anaerobic digestion has achieved full commercial maturity (TRL 9), while acidogenic fermentation remains mostly at TRL 6–7, and other pathways such as microbial protein or holocellulase production are still at early stages (TRL 3–4). High-value products, including polyhydroxyalkanoates (PHA) and succinic acid, are clustered at TRL 6–7, typically demonstrated at pilot scale, whereas hydrochar from hydrothermal carbonization has progressed up to TRL 8–9. Companies and projects confirm the feasibility of integrating biological, chemical, and thermal pathways into biorefineries, spanning a wide range of TRLs and showcasing their potential within the circular bioeconomy. Key gaps persist in scaling downstream processes for product purification, reducing costs, addressing feedstock variability, and optimizing pretreatment. By synthesizing experimental evidence with industrial demonstrations and sustainability assessments, this study provides a comprehensive perspective on how municipal biowaste can be converted into both non-fuel bioproducts and biofuels, thereby supporting circular bioeconomy strategies for future environmental policies. Graphical Abstract

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Late-phase depolarization and repolarization abnormalities in english bulldogs with phenotypic expression of arrhythmogenic cardiomyopathy - Mara Bagardi; Manuela Perego; Fabio M. Colombo; Alessandra Maffei; Paola G. Brambilla; Michele Polli; Giorgio Camozzini; Roberto A. Santilli (Veterinary Research Communications, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Paint particle pollution in aquatic environments: Current advances and analytical challenges - A.D. Forero-López; C.V. Colombo; A.P. Loperena; N.G. Morales-Pontet; A.C. Ronda; I.L. Lehr; G.E. De-la-Torre; M. Ben-Haddad; T.A. Aragaw; G. Suaria; G.N. Rimondino; F.E. Malanca; et al. (Journal of Hazardous Materials, 2024)

Has climate change over the last ten years caused a banalisation of diatom communities in Cypriot streams? - Marco Cantonati; David G. Armanini; Daniele Demartini; Athina Papatheodoulou; Olena P. Bilous; Federica Colombo; Nicola Angeli; Rosalina Stancheva; Gerald Dörflinger; Kalina M. Manoylov (Science of The Total Environment, 2024)

An aquaculture risk model to understand the causes and consequences of Atlantic Salmon mass mortality events: A review - Zaman Sajid; A. Kurt Gamperl; Christopher C. Parrish; Stefanie M. Colombo; Javier Santander; Charles Mather; Barbara Neis; Ingunn Marie Holmen; Ramón Filgueira; Cynthia H. McKenzie; Lissandra Souto Cavalli; Mohamed Jeebhay; et al. (Reviews in Aquaculture, 2024)
Mass mortality events (MMEs) are defined as the death of large numbers of fish over a short period of time. These events can result in catastrophic losses to the Atlantic salmon aquaculture industry and the local economy. However, they are challenging to understand because of their relative infrequency and the high number of potential factors involved. As a result, the causes and consequences of MMEs in Atlantic salmon aquaculture are not well understood. In this study, we developed a structural network of causal risk factors for MMEs for aquaculture and the communities that depend on Atlantic salmon aquaculture. Using the Interpretive Structural Modeling (ISM) technique, we analysed the causes of Atlantic salmon mass mortalities due to environmental (abiotic), biological (biotic) and nutritional risk factors. The consequences of MMEs were also assessed for the occupational health and safety of aquaculture workers and their implications for the livelihoods of local communities. This structural network deepens our understanding of MMEs and points to management actions and interventions that can help mitigate mass mortalities. MMEs are typically not the result of a single risk factor but are caused by the systematic interaction of risk factors related to the environment, fish diseases, feeding/nutrition and cage‐site management. Results also indicate that considerations of health and safety risk, through pre‐ and post‐event risk assessments, may help to minimize workplace injuries and eliminate potential risks of human fatalities. Company and government‐assisted socio‐economic measures could help mitigate post‐mass mortality impacts. Appropriate and timely management actions may help reduce MMEs at Atlantic salmon cage sites and minimize the physical and social vulnerabilities of workers and local communities.

Characterization of artificial rainfall produced by a portable rainfall simulator using a rotating dynamic rainfall gauge system - Antônio Reynaldo de Sousa Costa; Lívia Alves Alvarenga; Michael Silveira Thebaldi; Luiz Antonio Lima; Alberto Colombo; Daniel Green; Jorge M. G. P. Isidoro (Hydrological Sciences Journal, 2024)

Zircon U-Pb and Lu-Hf isotopes reveal the crustal evolution of the SW Angolan Shield (Congo Craton) - Ezequiel Ferreira; Jérémie Lehmann; José Feliciano Rodrigues; Ben Hayes; Enrique Merino-Martínez; Lorenzo Milani; Grant M. Bybee; Trishya M. Owen‑Smith; José Luis García-Lobón; Colombo C. G. Tassinari; Henriette Ueckermann; Kei Sato; et al. (Gondwana Research, 2024)

Assessment of meso- and microplastics distribution in coastal sediments and waters at the middle estuary of the Rio De La Plata, Argentina (SW Atlantic Ocean) - L. Santucci; M.D. Fernández-Severini; G.N. Rimondino; C.V. Colombo; G. Prieto; A.D. Forero-López; E.S. Carol (Science of The Total Environment, 2024)

The use of a complex tetra-culture alveolar model to study the biological effects induced by gold nanoparticles with different physicochemical properties - Melissa Saibene; Tommaso Serchi; Patrizia Bonfanti; Anita Colombo; Inge Nelissen; Rashi Halder; Jean-Nicolas Audinot; Beatriz Pelaz; Mahmoud G. Soliman; Wolfgang J. Parak; Paride Mantecca; Arno C. Gutleb; et al. (Environmental Toxicology and Pharmacology, 2024)

High-resolution temporal variations of nitrate in a high-elevation pond in alpine tundra (NW Italian Alps) - N. Colombo; R. Balestrini; D. Godone; D. Vione; D. Said-Pullicino; G. Viviano; M. Martin; C.A. Delconte; S. Fratianni; A.G. Capodaglio; E. Pintaldi; M. Freppaz; et al. (CATENA, 2024)

P25-21: Approach and challenges in the toxicological and allergenicity risk assessment of novel proteins and their sources - I. Nuin Garciarena; O. Albert; P. Colombo; A. Fernández Dumont; M. Laganaro; A. Muñoz González; E. Noriega Fernández; G. Precup; R. Roldán Torres; A. Rossi; E. Ververis; A. Germini; et al. (Toxicology Letters, 2023)

Modeling the compressive strength of metakaolin-based geopolymers based on the statistical analysis of experimental data - M. Muracchioli; G. Menardi; M. D' Agostini; G. Franchin; P. Colombo (Applied Clay Science, 2023)

The paleoenvironmental and thermal histories of the Permian Irati Formation shale in the Paraná Basin, Brazil: An integrated approach based on mineralogical and organic imprints - Haline V. Rocha; Lucy G. Sant’Anna; Cristina F.A. Rodrigues; Márcia Mendes; Zélia Pereira; Gilda Lopes; Paulo Fernandes; Egberto Pereira; Colombo C.G. Tassinari; Manuel J. Lemos de Sousa (Marine and Petroleum Geology, 2023)

Chemical-analytical characterization and leaching of heavy metals associated with nanoparticles and microplastics from commercial face masks and the abundance of personal protective equipment (PPE) waste in three metropolitan cities of South America - A.D. Forero López; G.E. De-la-Torre; M.D. Fernández Severini; G. Prieto; L.I. Brugnoni; C.V. Colombo; D.C. Dioses-Salinas; G.N. Rimondino; C.V. Spetter (Marine Pollution Bulletin, 2023)

Study of the mechanical properties of thermoplastic polyurethane (TPU) recycled from end-of-life ski-boots and techno-economic analysis (TEA) of the mechanical recycling processes - A. Nanni; L. Crosetta; G. La Fauci; F. Biagi; M. Parisi; D. Colombo; M. Colonna (Sustainable Chemistry and Pharmacy, 2023)

Colostrum quality associations with passive immunity transfer in foals - H B Magalhães; G Araujo; I Colombo; K M Spencer; G Podico; I F Canisso (Journal of Equine Veterinary Science, 2023)

: A high-order discontinuous Galerkin solver for flow simulations and multi-physics applications - E. Ferrer; G. Rubio; G. Ntoukas; W. Laskowski; O.A. Mariño; S. Colombo; A. Mateo-Gabín; H. Marbona; F. Manrique de Lara; D. Huergo; J. Manzanero; A.M. Rueda-Ramírez; et al. (Computer Physics Communications, 2023)

Assessing the role of REM13, REM34 and REM46 during the transition to the reproductive phase in Arabidopsis thaliana - Silvia Manrique; Francesca Caselli; Luis Matías-Hernández; Robert G. Franks; Lucia Colombo; Veronica Gregis (Plant Molecular Biology, 2023)
REM (reproductive meristem) transcription factors have been proposed as regulators of plant reproductive development mainly based on their specific expression patterns in reproductive structures, but their roles are still largely unknown probably because of their redundancy. We selected three REM genes ( REM13 , REM34 and REM46 ) for functional analysis, based on their genome position and/or co-expression data. Our results suggest that these genes have a role in flowering time regulation and may modulate cell cycle progression. In addition, protein interaction experiments revealed that REM34 and REM46 interact with each other, suggesting that they might work cooperatively to regulate cell division during inflorescence meristem commitment. Previous attempts of using co-expression data as a guide for functional analysis of REMs were limited by the transcriptomic data available at the time. Our results uncover previously unknown functions of three members of the REM family of Arabidopsis thaliana and open the door to more comprehensive studies of the REM family, where the combination of co-expression analysis followed by functional studies might contribute to uncovering the biological roles of these proteins and the relationship among them.

Identification of IPT9 in Brachiaria brizantha (syn. Urochloa brizantha) and expression analyses during ovule development in sexual and apomictic plants - Luciana G. Ferreira; Diva M. A. Dusi; André S. T. Irsigler; Ana C. M. M. Gomes; Lilian H. Florentino; Marta A. Mendes; Lucia Colombo; Vera T. C. Carneiro (Molecular Biology Reports, 2023)
Background In Brachiaria sexual reproduction, during ovule development, a nucellar cell differentiates into a megaspore mother cell (MMC) that, through meiosis and mitosis, gives rise to a reduced embryo sac. In aposporic apomictic Brachiaria , next to the MMC, other nucellar cells differentiate into aposporic initials that enter mitosis directly forming an unreduced embryo sac. The IPT (isopentenyltransferase) family comprises key genes in the cytokinin (CK) pathway which are expressed in Arabidopsis during ovule development. BbrizIPT9 , a B. brizantha ( syn. Urochloa brizantha ) IPT9 gene, highly similar to genes of other Poaceae plants, also shows similarity with Arabidopsis IPT9, AtIPT9 . In this work, we aimed to investigate association of BbrizIPT9 with ovule development in sexual and apomictic plants. Methods and results RT-qPCR showed higher BbrizIPT9 expression in the ovaries of sexual than in the apomictic B. brizantha . Results of in-situ hybridization showed strong signal of BbrizIPT9 in the MMC of both plants, at the onset of megasporogenesis. By analyzing AtIPT9 knockdown mutants, we verified enlarged nucellar cell, next to the MMC, in a percentage significantly higher than in the wild type, suggesting that knockout of AtIPT9 gene triggered the differentiation of extra MMC-like cells. Conclusions Our results indicate that AtIPT9 might be involved in the proper differentiation of a single MMC during ovule development. The expression of a BbrizIPT9 , localized in male and female sporocytes, and lower in apomicts than in sexuals, and effect of IPT9 knockout in Arabidopsis, suggest involvement of IPT9 in early ovule development.

Baseline assessment of microplastics in commercially important marine bivalves from New York, U.S.A. - Mackenzie L. Minder; Isabella G. Colombo; Konstantine J. Rountos (Marine Pollution Bulletin, 2023)

Correction to: The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2023)

Database development and survival analysis in a clinical and historical cohort of dogs affected by myxomatous mitral valve disease treated or not with pimobendan using causal inference techniques - Mara Bagardi; Valentina Palermo; Chiara Locatelli; Fabio Maria Colombo; Laura Pazzagli; Paola G. Brambilla (Veterinary Research Communications, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Gulliver’s virtual travels: active embodiment in extreme body sizes for modulating our body representations - S. Serino; F. Scarpina; A. Chirico; A. Dakanalis; D. Di Lernia; D. Colombo; V. Catallo; E. Pedroli; G. Riva (Cognitive Processing, 2020)
It is noted that the perceptual experience of body and space can be modulated by changing the action capabilities or by manipulating the perceived body dimensions through a multisensory stimulation. This study adds to pre-existing literature by investigating the alterations in bodily experience following embodiment to both enlarged and shrunked bodies, while participants actively navigated in a virtual environment. A normal-sized body served as a reference condition. After each embodied navigation, participants estimated the height and width of three different body parts. Results revealed that the embodiment over shrunked body induced a significant reduction in participants’ body image, while no changes were reported after the embodiment over the enlarged body. Findings were discussed in terms of previous literature exploring the constraints implicated in the ownership over different bodies.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Short-Term Effects of Genetically Modified Potato on Arbuscular Mycorrhizal Fungal Communities - Betina I. Stephan; Roxana P. Colombo; Vanesa A. Silvani; Mariana Pérgola; Alicia M. Godeas; Alejandro G. Pardo; Laura Fernández Bidondo (Journal of Soil Science and Plant Nutrition, 2019)

Synthesis and evaluation of the antileishmanial activity of silver compounds containing imidazolidine-2-thione - Patrícia Ferreira Espuri; Larissa Luiza dos Reis; Eduardo de Figueiredo Peloso; Vanessa Silva Gontijo; Fábio Antônio Colombo; Juliana Barbosa Nunes; Carine Ervolino de Oliveira; Eduardo T. De Almeida; Débora E. S. Silva; Jessica Bortoletto; Daniel Fonseca Segura; Adelino V. G. Netto; et al. (JBIC Journal of Biological Inorganic Chemistry, 2019)

In Situ Tissue Labeling of Cerebral Amyloid Using HIV-Related Tat Peptide - E. Maderna; L. Colombo; A. Cagnotto; G. Di Fede; A. Indaco; F. Tagliavini; M. Salmona; G. Giaccone (Molecular Neurobiology, 2018)

Nanoemulsion-Loaded Hydrogels for Topical Administration of Pentyl Gallate - Regina G. Kelmann; Mariana Colombo; Ricardo J. Nunes; Cláudia M. O. Simões; Letícia S. Koester (AAPS PharmSciTech, 2018)

Ambrosia pollen source inventory for Italy: a multi-purpose tool to assess the impact of the ragweed leaf beetle (Ophraella communa LeSage) on populations of its host plant - M. Bonini; Branko Šikoparija; C. A. Skjøth; G. Cislaghi; P. Colombo; C. Testoni; M. Smith (International Journal of Biometeorology, 2018)

Effects of aerobic exercise training on metabolism of nitric oxide and endothelin-1 in lung parenchyma of rats with pulmonary arterial hypertension - A. Zimmer; R. B. Teixeira; J. H. P. Bonetto; R. Siqueira; C. C. Carraro; L. M. Donatti; A. Hickmann; I. E. Litvin; A. E. G. Godoy; A. S. Araujo; R. Colombo; Adriane Belló-Klein (Molecular and Cellular Biochemistry, 2017)

The growth and contamination mechanism of the Cana Brava layered mafic-ultramafic complex: new field and geochemical evidences - Tommaso Giovanardi; Vicente A. V. Girardi; Ciro T. Correia; Silvano Sinigoi; Colombo C. G. Tassinari; Maurizio Mazzucchelli (Mineralogy and Petrology, 2017)

Healthy and tumoral tissue resistivity in wild-type and sparc–/– animal models - D. Meroni; G. Mauri; D. Bovio; A. M. Bianchi; C. Chiodoni; M. P. Colombo; E. Meroni; A. Aliverti (Medical & Biological Engineering & Computing, 2016)

A follow-up study examining airborne Ambrosia pollen in the Milan area in 2014 in relation to the accidental introduction of the ragweed leaf beetle Ophraella communa - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; Ł. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2016)

The thyroid status reprograms T cell lymphoma growth and modulates immune cell frequencies - H. A. Sterle; M. L. Barreiro Arcos; E. Valli; M. A. Paulazo; S. P. Méndez Huergo; A. G. Blidner; F. Cayrol; M. C. Díaz Flaqué; A. J. Klecha; V. A. Medina; L. Colombo; G. A. Rabinovich; et al. (Journal of Molecular Medicine, 2016)

Is the recent decrease in airborne Ambrosia pollen in the Milan area due to the accidental introduction of the ragweed leaf beetle Ophraella communa? - M. Bonini; B. Šikoparija; M. Prentović; G. Cislaghi; P. Colombo; C. Testoni; L. Grewling; S. T. E. Lommen; H. Müller-Schärer; M. Smith (Aerobiologia, 2015)

Continuous streamflow simulation for index flood estimation in an Alpine basin of northern Italy - G. Ravazzani; D. Bocchiola; B. Groppelli; A. Soncini; M.C. Rulli; F. Colombo; M. Mancini; R. Rosso (Hydrological Sciences Journal, 2015)

Timing of multiple hydrothermal events in the iron oxide–copper–gold deposits of the Southern Copper Belt, Carajás Province, Brazil - Carolina P. N. Moreto; Lena V. S. Monteiro; Roberto P. Xavier; Robert A. Creaser; S. Andrew DuFrane; Gustavo H. C. Melo; Marco A. Delinardo da Silva; Colombo C. G. Tassinari; Kei Sato (Mineralium Deposita, 2015)

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

Combined effects of arbuscular mycorrhizal fungi and exogenous cytokinins on pomegranate (Punica granatum) under two contrasting water availability conditions - M. J. Bompadre; L. Fernández Bidondo; V. A. Silvani; R. P. Colombo; M. Pérgola; A. G. Pardo; A. M. Godeas (Symbiosis, 2015)

AtAPOSTART1, an Arabidopsis thaliana PH-START domain protein involved in seed germination - F. Resentini; S. Vanzulli; G. Marconi; L. Colombo; E. Albertini; S. Masiero (Plant Biosystems, 2014)

B25716/1: a novel albumin-binding Gd-AAZTA MRI contrast agent with improved properties in tumor imaging - E. Gianolio; C. Cabella; S. Colombo Serra; G. Valbusa; F. Arena; A. Maiocchi; L. Miragoli; F. Tedoldi; F. Uggeri; M. Visigalli; P. Bardini; S. Aime (JBIC Journal of Biological Inorganic Chemistry, 2014)

Apple ( Malus domestica L. Borkh) as an emerging model for fruit development - G. Eccher; S. Ferrero; F. Populin; L. Colombo; A. Botton (Plant Biosystems, 2014)

Differential efficiency of two strains of the arbuscular mycorrhizal fungus Rhizophagus irregularis on olive (Olea europaea) plants under two water regimes - M. J. Bompadre; M. C. Rios De Molina; R. P. Colombo; L. Fernandez Bidondo; V. A. Silvani; A. G. Pardo; J. A. Ocampo; A. M. Godeas (Symbiosis, 2013)

The relationship between carbonate facies, volcanic rocks and plant remains in a late Palaeozoic lacustrine system (San Ignacio Fm, Frontal Cordillera, San Juan province, Argentina) - P. Busquets; I. Méndez-Bedia; G. Gallastegui; F. Colombo; R. Cardó; O. Limarino; N. Heredia; S. N. Césari (International Journal of Earth Sciences, 2013)

Heme oxygenase 1 (HO-1) challenges the angiogenic switch in prostate cancer - M. Ferrando; G. Gueron; B. Elguero; J. Giudice; A. Salles; F. Coluccio Leskow; E. A. Jares-Erijman; L. Colombo; R. Meiss; N. Navone; A. De Siervi; E. Vazquez (Angiogenesis, 2011)

Pingüino In-bearing polymetallic vein deposit, Deseado Massif, Patagonia, Argentina: characteristics of mineralization and ore-forming fluids - Sebastián M. Jovic; Diego M. Guido; Isidoro B. Schalamuk; Francisco J. Ríos; Colombo C. G. Tassinari; Clemente Recio (Mineralium Deposita, 2011)

Metamorphic P-T evolution of granulites in the central Ribeira Fold Belt, SE Brazil - Telmo M. Bento dos Santos; José M. Munhá; Colombo C. G. Tassinari; Paulo E. Fonseca; Coriolano Dias Neto (Geosciences Journal, 2011)

With time on our side? Task-dependent compensatory processes in graceful aging - M. Berlingeri; G. Bottini; L. Danelli; F. Ferri; D. Traficante; L. Sacheli; N. Colombo; M. Sberna; R. Sterzi; G. Scialfa; E. Paulesu (Experimental Brain Research, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

3-D distribution of nongeniculate corallinales: a case study from a reef crest of South Sinai (Red Sea, Egypt) - A. Caragnano; F. Colombo; G. Rodondi; D. Basso (Coral Reefs, 2009)

Novel Platforms for Oral Drug Delivery - P. Colombo; F. Sonvico; G. Colombo; R. Bettini (Pharmaceutical Research, 2009)

Acoustic survey of a jellyfish-dominated ecosystem (Mljet Island, Croatia) - G. Alvarez Colombo; A. Benović; A. Malej; D. Lučić; T. Makovec; V. Onofri; M. Acha; A. Madirolas; H. Mianzan (Hydrobiologia, 2009)

Leaf level early assessment of ozone injuries by passive fluorescence and photochemical reflectance index - M. Meroni; V. Picchi; M. Rossini; S. Cogliati; C. Panigada; C. Nali; G. Lorenzini; R. Colombo (International Journal of Remote Sensing, 2008)

Influence of vestibular and visual stimulation on split-belt walking - B. Marques; G. Colombo; R. Müller; M. R. Dürsteler; V. Dietz; D. Straumann (Experimental Brain Research, 2007)

Genetic diversity and structure of Ethiopian, Yemen and Brazilian Coffea arabica L. accessions using microsatellites markers - Milene Silvestrini; Michele G. Junqueira; Andréa C. Favarin; Oliveiro Guerreiro-Filho; Mirian P. Maluf; Maria B. Silvarolla; Carlos A. Colombo (Genetic Resources and Crop Evolution, 2007)

Cost-effectiveness of pneumococcal vaccination for prevention of invasive pneumococcal disease in the elderly: an update for 10 Western European countries - S. M. A. A. Evers; A. J. H. A. Ament; G. L. Colombo; H. B. Konradsen; R. R. Reinert; D. Sauerland; K. Wittrup-Jensen; C. Loiseau; D. S. Fedson (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Bud and crown architecture of white spruce and black spruce - Stephen J. Colombo; Colin W. G. Templeton (Trees, 2006)

CT—3D rotational angiography automatic registration: A sensitivity analysis - J. Stancanello; C. Cavedon; P. Francescon; P. Cerveri; G. Ferrigno; F. Causin; F. Colombo (Medical & Biological Engineering & Computing, 2005)

EU-OSTID: A Collection of Transposon Insertional Mutants for Functional Genomics in Rice - L. J. G van Enckevort; Gaëtan Droc; Pietro Piffanelli; Raffaella Greco; Cyril Gagneur; Christele Weber; Víctor M. González; Pere Cabot; Fabio Fornara; Stefano Berri; Berta Miro; Ping Lan; et al. (Plant Molecular Biology, 2005)

First lead isotopic data for cinnabar in the Almadén district (Spain): implications for the genesis of the mercury deposits - Pablo Higueras; José Munhá; Roberto Oyarzun; Colombo C. G. Tassinari; Izabel R. Ruiz (Mineralium Deposita, 2005)

Robot-aided neurorehabilitation of the upper extremities - R. Riener; T. Nef; G. Colombo (Medical & Biological Engineering & Computing, 2005)

Single joint perturbation during gait: neuronal control of movement trajectory - V. Dietz; G. Colombo; R. Mller (Experimental Brain Research, 2004)

A Preliminary Trial Using Multi-target Polymerase Chain Reaction (multiplex PCR) and Restriction Fragment Length Polymorphism (PCR-RFLP) on the Same Feedstuffs to Detect Tissues of Animal Origin - F. Colombo; E. Marchisio; I.E. Trezzi; V. Peri; L. Pinotti; A. Baldi; G. Soncini (Veterinary Research Communications, 2004)

Ovule-specific MADS-box proteins have conserved protein-protein interactions in monocot and dicot plants - R. Favaro; R. Immink; V. Ferioli; B. Bernasconi; M. Byzova; G. Angenent; M. Kater; L. Colombo (Molecular Genetics and Genomics, 2002)

Sequence comparison and phylogenetic analysis of fish nodaviruses based on the coat protein gene - L. Dalla Valle; E. Negrisolo; P. Patarnello; L. Zanella; C. Maltese; G. Bovo; L. Colombo (Archives of Virology, 2001)

Feeding on survival-food: gelatinous plankton as a source of food for anchovies - H. Mianzan; M. Pájaro; G. Alvarez Colombo; A. Madirolas (Hydrobiologia, 2001)

Effects of diet supplementation with carp ovary on gonad differentiation and growth of the European eel - G. Grandi; F. Poerio; G. Colombo; M. Chicca (Journal of Fish Biology, 2000)
Treating elvers of European eel Anguilla anguilla with mature carp ovary for 3–6 months during early growth induced female differentiation in 51·6–66·7% of treated animals compared with c . 5% in controls. The treatment also induced differentiation of ovaries in eels L T and a higher number of Syrski organs with ambisexual characters, and was most effective when administered at an early growth stage. The results could be attributed to the natural steroid content of the carp ovary. The total weight of treated animals at the end of the farm experiment was 84·7% higher than controls. The specific growth rate for weight was significantly higher in female yellow eels than in males, for both control and treated groups. The enhanced growth was related to induced feminization. A diet supplementation with mature carp ovary could be a good approach to control of sex differentiation and growth in eels.

Effect of drying methods on retention of moist sucralfate gel properties - L. Maggi; P. L. Catellani; E. Fisicaro; P. Santi; F. Zani; G. Massimo; P. Colombo (AAPS PharmSciTech, 2000)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Free circulating magnesium and loop diuretics in humans - T. Gozzi; S. Dürler; A. C. Truttman; J. P. Colombo; M. G. Bianchetti (European Journal of Clinical Pharmacology, 1997)

Characterization of the ethanol-like discriminative stimulus effects of 5-HT receptor agonists as a function of ethanol training dose - K. A. Grant; G. Colombo; Gregory J. Gatto (Psychopharmacology, 1997)

Exopolysaccharide of Nostoc muscorum (Cyanobacteria) in the aggregation of soil particles - G. Zulpa de Caire; M. Storni de Cano; M. C. Zaccaro de Mulé; R. M. Palma; K. Colombo (Journal of Applied Phycology, 1997)

Characterization of a biofilter treating toluene contaminated air - V. Andreoni; G. Origgi; M. Colombo; E. Calcaterra; A. Colombi (Biodegradation, 1997)

1,2-Dichloropropane (DCP) toxicity is correlated with DCP-induced glutathione (GSH) depletion and is modulated by factors affecting intracellular GSH - R. Imberti; A. Mapelli; P. Colombo; P. Richelmi; F. Bertè; G. Bellomo (Archives of Toxicology, 1990)